Odprti pouk pri predmetu spoznavanje okolja - Ivanuš-Grmek, Milena (Sodobna pedagogika, 2006)
The article presents the results of research conducted in spring 2005 on a sample of teachers in the first three years of the nine-year primary school. We wanted to know which didactic strategies teachers use in their classes on environmental education, how frequently they use them and whether there are statistically significant differences between teachers in the frequency of using individual didactic strategies with regard to the time of the school's introduction of the nine-year programme. The results of the research work indicate that in these classes teachers use different didactic strategies, and the frequency of using individual didactic strategies mostly does not depend on the time of the school's introduction of the nine-year programme.
Keywords: osnovne šole; razredni pouk; spoznavanje okolja; devetletka; metodika; pouk